The nature of domestic and family violence reported to child protection prenatally. (January 2021) - Meiksans, Jenna; McDougall, Stewart; Arney, Fiona; Flaherty, Rosemaria; Chong, Alwin; Ward, Fiona; Taylor, Cathy
Highlights: First Australian study to examine the nature of violence in prenatal reports. Violence experienced within families reported prenatally was severe. Violence prevention efforts are a key pillar of child protection repsonses. Abstract: Up to 70% of prenatal child protection reports include notifier concerns about current or previous domestic and family violence within families, far more than identified using only fixed-field administrative data. The nature of this violence remains unknown. A qualitative case file review was carried out to examine the nature of violence recorded in the narratives of 91 prenatal child protection reports from a single Australian jurisdiction in 2014. Concerns raised to child protection were coded, and similar codes categorised to identify the main ways in which violence was recorded within the reports. Five themes emerged: the nature of the violence; violence in the context of relationships; violence resulting in police and court intervention; co-occurring experiences of violence within families; and incidents or patterns of violence that lacked detailed description. Violence experienced within families was severe, including allegations of attempted murder, and pervasive, occurring in multiple ways within families and across the population. Findings suggest violence prevention and service responses are a key pillar of any approach to the early intervention and prevention of child abuse and neglect, and that improved understandings of the emergence and patterns of violence experienced are critical in developing targeted interventions.